KEPATUHAN SISWA SMA MUHAMMADIYAH 15 JAKARTA TERHADAP PENERAPAN PROTOKOL KESEHATAN COVID-19 TAHUN 2021 - Rifdah Amalia Salsabila; Sarah Handayani; Elia Nur A’Yunin (Universitas Islam Kalimantan Muhammad Arsyad Al-Banjari Banjarmasin, 2023)
During the COVID-19 pandemic, preventive measures are the only effective way to deal with COVID-19, which requires a level of compliance with health protocols. Objective of this study was to determine the factors related to student compliance with the implementation of the COVID-19 health protocol in 2021. The population in this study were students aged 15-18 years with a total sample of 235 respondents. The study design used was cross sectional with the sampling technique using proportional stratified random sampling. The data used in this study is primary data. And the data analysis used is thetest chi-square. in this study indicate that there is a relationship between knowledge (p-value= 0.026), attitude (p-value= 0.017), cues to action (p-value= 0.008), and self-efficacy (p-value= 0.006) with student compliance with application of health protocols, and showed no significant relationship between student age (p-value= 0.071), gender (p-value= 0.278), perceived susceptibility (p-value= 0.341), perceived severity (p-value=1,000), perceived benefits (p-value=0.974), perceived barriers (p-value=0.174) with student compliance with the implementation of the COVID-19 health protocol. obtained in this study is that there is a relationship between knowledge, attitudes, cues to action, and self-efficacy with student compliance with the implementation of the COVID-19 health protocol.